EMG evaluation of hip adduction exercises for soccer players: implications for exercise selection in prevention and treatment of groin injuries - Serner, A.; Jakobsen, M. D.; Andersen, L. L.; Hölmich, P.; Sundstrup, E.; Thorborg, K. (British Journal of Sports Medicine, 2014)
Introduction Exercise programmes are used in the prevention and treatment of adductor-related groin injuries in soccer; however, there is a lack of knowledge concerning the intensity of frequently used exercises.